2016
DOI: 10.1007/978-3-319-43139-0_6
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial Carcinoma: Specific Targeted Pathways

Abstract: Endometrial cancer (EC) is the most common gynecologic malignancy in the western world with more than 280,000 cases per year worldwide. Prognosis for EC at early stages, when primary surgical resection is the most common initial treatment, is excellent. Five-year survival rate is around 70 %.Several molecular alterations have been described in the different types of EC. They occur in genes involved in important signaling pathways. In this chapter, we will review the most relevant altered pathways in EC, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 342 publications
0
38
0
Order By: Relevance
“…As reported, cancerous human endometrium expresses lower levels of TGFBR1 protein [47,52]. TGFBR2 is mutated/altered in 6.5% of endometrial tumours [49,51]. Studies from The Cancer Genome Atlas Research Network have also suggested alterations of several SMADs in human endometrial cancer [49,51].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…As reported, cancerous human endometrium expresses lower levels of TGFBR1 protein [47,52]. TGFBR2 is mutated/altered in 6.5% of endometrial tumours [49,51]. Studies from The Cancer Genome Atlas Research Network have also suggested alterations of several SMADs in human endometrial cancer [49,51].…”
Section: Discussionmentioning
confidence: 94%
“…It has been shown that mutations of TGFB signalling components, including TGFB receptors and SMADs, and alteration of TGFB signalling activity reflected by changes in gene expression and/or phosphorylation of key signalling proteins play a role in the patho-aetiology of human endometrial cancer [47,49,50]. TGFBR1 has a 5.6% mutation and alteration rate in human endometrial cancer [49,51]. As reported, cancerous human endometrium expresses lower levels of TGFBR1 protein [47,52].…”
Section: Discussionmentioning
confidence: 99%
“…Among its targets, AKT phosphorylates and inhibits tuberous sclerosis complex 2 (TSC2) within the TSC complex, which indirectly inhibits mTOR complex 1 (mTORC1). PI3K-AKT signaling activates mTORC1 [ 56 ], a key regulator of metabolism and biosynthetic processes, including activation of hypoxia-inducible factor 1 (HIF1) and other transcription factors. HIF1 stimulates glucose transporter expression on the cell surface, thereby increasing cellular glucose influx, and shifts metabolic pathways towards glycolysis through inhibitory mitochondrial pyruvate dehydrogenase kinase activation [ 49 , 57 ].…”
Section: Reviewmentioning
confidence: 99%
“…A number of previous reviews have discussed signalling pathways involved in homeostasis of the endometrium and various pathologies, and two recent reviews have examined Wnt inhibitors in pre-clinical settings but with limited discussion of implications for endometrial cancer (Eritja et al 2017, Katoh & Katoh 2017. Previous reviews have focused on β-catenin-dependent Wnt signalling with no discussion of the β-catenin-independent receptors Classification Historically, endometrial cancer was classified into two distinct subtypes known as Bokhman type one and type two (Bokhman 1983).…”
Section: Introductionmentioning
confidence: 99%